Electronic Structures and Magnetic Properties of Zigzag VS2 Single-Layer Nanoribbons - Hongyu Deng; Guangming Fu; Dongyong Shan; Wei Chen; Jianming Zhang (Advances in Condensed Matter Physics)
Inspired by the fabrication of zigzag MoSe2 nanoribbons and MoS2 nanoribbons with well-defined atomically precise edges, we study the stability, electronic structures, and magnetic properties of zigzag VS2 nanoribbons (ZNRs) with different edge structures and widths. The calculated edge energies for all studied VS2 nanoribbons are less than 0.9 eV/Å, lower than that of fabricated armchair and zigzag graphene nanoribbons, indicating the easy formation of ZNRs. The results show N-ZNRs terminated with S and V atoms (N-SV-ZNRs) is a ferrimagnetic metal. The magnetic moments are mainly contributed by d orbitals of V atoms, and the V2 atom exhibits a spin that is antiparallel to the other V atoms due to the increase of through–space interaction. With hydrogen passivation, the magnetic moment of V2 atom in N-SV-ZNRs couples ferromagnetically with other V atoms and N-SV-ZNRs becomes half metallic. The N-ZNRs terminated with V atom (N-VV-ZNRs) is found to be a magnetic metal, and the magnetic moments of V atoms around edges are very sensitive to ribbon width. Furthermore, N-ZNRs with S atom terminations (N-SS-ZNRs) is a ferromagnetic quasi-semiconductor. Only select bands intersect with the Fermi level near the Γ point, and the magnetic moments of all V atoms couple ferromagnetically. These findings are essential for applications of VS2 nanoribbons–based low-dimensional spintronic devices.